Analysis of Information Security in Public Entities of Colombia 2020-2022 (2022)
Information in public entities is a public good that must be protected. The three pillars of information security must be applied to it: confidentiality, integrity and availability to prevent possible cyber threats. It is for this reason that the Government has defined the guidelines to implement the information security management system to preserve it, preventing it from being put at risk and destabilizing the fulfillment of the processes and the management of the entities. Through the Online Government Policy and with the Ministry of Information and Communication Technologies - MinTIC, the Information Security and Privacy Model (MSPI) is created and with the Risk Management and Control Design issued by the DAFP, is how the Administrative Department of the Presidency of the Republic (DAPRE) adopts the system to improve information security practices, prevent and detect cyber-attacks. Likewise, for the security of this asset, it is necessary for the management, control, and decision-making by the Public Entities of Colombia to establish the policies that will allow the execution of the security models together with strategies that minimize the risk loss and theft of information.